STUDI KANDUNGAN NUTRISI LIMBAH MEDIA TANAMJAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) UNTUK PAKAN TERNAK RUMINANSIA - Eko Yuliastuti ES; Adhi Susilo (LPPM Universitas Terbuka, 2003)
Growth media waste of white oyster mushroom cultivation can be used as ruminant feed. We observed the nutrient content of the growth media waste. The focus is on the protein, carbohydrate, mineral and crude fiber. The protein, calcium and phosphor content of white oyster mushroom growth media waste is higher than the protein content in the media before it was used for mushroom cultivation. However, the fat content is lower after the media was used than control (the media before it was used). The difference is caused by microorganism degradation. The growth media waste can be used as ruminant feed up to 75 % of total forage dry matter without any negative effect.